Comparing Mouse and Human Tissue-Resident γδ T Cells - Qu, Guanyu; Wang, Shengli; Zhou, Zhenlong; Jiang, Dawei; Liao, Aihua; Luo, Jing (Frontiers in Immunology, 2022)
Although the functions of circulating immune cell compartments have been studied in detail for decades, limitations in peripheral tissue access and cell yield limit our understanding of tissue-based immunity, especially in gamma delta T cells. γδ T cells are a unique subset of T cells that are rare in secondary lymphoid organs but enriched in many peripheral tissues including skin, uterus, and other epithelial tissues. In addition to immune surveillance activities, recent reports have revealed exciting new roles for γδ T cells in homeostatic tissue physiology in mouse or human species, respectively. It will be important to investigate to what extent the developmental rules dissected in mouse models apply to human γδ T cells. Besides, it is also necessary to understand the development or biogenesis differences between human and mouse γδ T cells. To better understanding how γδ T cells are maintained in physiological and pathological circumstances within different tissues, dissect the progenitors of different tissue resident γδ T cells is a vital aspect of γδ T cell biology as well. Here, we summarize current knowledge of the γδ T phenotype in various tissues in mice and humans, aiming to elucidate the similarities and differences of tissue-resident gamma delta T cells between human and mouse species.